Enhancing health and well-being: unlocking the speed abilities of 9-year-old primary school children - Margarita Mameshina; Mirosława Cieślicka (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. Physical activity is the key to fostering healthy growth and development in children. Encouraging children to engage in activities that enhance their speed abilities not only boosts their physical fitness but also contributes to their mental and emotional well-being. The purpose of the study - exploring speed abilities: a comparative study of 9-year-old primary school children in Ukraine and beyond.